A FELZÁRKÓZÁS KULCSA: VISEGRÁD PLUSZ EGYÜTTMŰKÖDÉS - Plósz, Dániel János (Közép-Európai Közlemények, 2019)
The study presents the necessary factors for Visegrad Cooperation how to become a regional hegemon. Poland is perhaps the most important country of Central and Eastern Europe, both in terms of population and economic strength, but its ability to enforce its interests may be much stronger within the framework of Visegrad Cooperation as one of its leading powers. The Visegrad countries are connected to the sea via Poland, but further expansion of the partnership is proposed with the involvement of Croatia and Romania, for strategic reasons. The 6 countries mentioned above together cover the coasts of three seas and a significant part of Central Europe, ie, due to their geographical location, they could become an inevitable factor in building the appropriate infrastructure background. As is known, infrastructure development is a key element of real economic convergence, but other factors are also relevant for catching up. Developing education systems, supporting domestic owned SMEs and large companies, increasing export opportunities, and favoring renewable energy sources, especially the latter, can make a significant contribution to successful catch-up. This is also evidenced by the results of other authors' analyzes and the econometric model used in this study. The development of health, social protection and recreational activities can also make a significant contribution to economic growth. The structure of hungarian budgetary expenditures and revenues is growth-friendly, it fulfills most of the criteria mentioned above.